Cropland non-agriculturization and agricultural green development: Evidence from the Yangtze River Economic Belt, China - Chunxia Zhu; Yangyang Sun; Haolun Xu (Heliyon)
As a carrier of agricultural production, the transformation of cropland non-agriculturalization (CLN) poses a significant challenge to the green development of agriculture. Although the impact of CLN on green development is acknowledged, empirical studies that establish a causal relationship are still relatively limited. This study leverages the land use remote sensing data to quantify the extent of CLN within the Yangtze River Economic Belt (YEB) of China. Employing the biennial non-radial directional distance function and Luenberger index, the agricultural green total factor productivity (AGTFP) has been measured under the dual constraints of “carbon source” and “carbon sink”. Subsequently, the double fixed effect model is utilized to examine the causal dynamics between CLN and AGTFP. The results reveal that the CLN in the YEB is predominantly manifested through the conversion of cropland to forest and construction land, exhibiting a decelerating trend and pronounced spatial disparities. Additionally, this article also confirms that the CLN process is accompanied by the intensification of cropland fragmentation, leading to diminished production efficiency. Concurrently, there is an increase in the intensity of fertilizer application, resulting in redundant inputs and poor environmental performance. These compounding effects ultimately hinder the growth of AGTFP. Given the economic vitality and ecological diversity of the YEB, the results of this study can provide reference for the protection of cropland and agricultural green development in other regions with prominent human-land contradictions worldwide.